2015
DOI: 10.1002/lary.25102
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pH and oxygen on biofilm formation in acute otitis media associated NTHi clinical isolates

Abstract: NA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 23 publications
3
7
0
Order By: Relevance
“…Although the two oxygen tension conditions tested provided a good development of biofilms, in quantitative tests, the condition of microaerophilia was superior to the condition of aerobiosis, particularly in biofilms formed using HAM-F12. A similar profile was observed by Osgood et al (2015) for the biofilms of Haemophilus influenzae formed in the condition of microaerophilia and with neutral pH. H. capsulatum , being a systemic pathogen, can develop in different regions of the body and with different oxygen tensions, therefore, verifying the influence of a lower or higher oxygen concentration in the development of biofilms is of paramount importance.…”
Section: Discussionsupporting
confidence: 74%
“…Although the two oxygen tension conditions tested provided a good development of biofilms, in quantitative tests, the condition of microaerophilia was superior to the condition of aerobiosis, particularly in biofilms formed using HAM-F12. A similar profile was observed by Osgood et al (2015) for the biofilms of Haemophilus influenzae formed in the condition of microaerophilia and with neutral pH. H. capsulatum , being a systemic pathogen, can develop in different regions of the body and with different oxygen tensions, therefore, verifying the influence of a lower or higher oxygen concentration in the development of biofilms is of paramount importance.…”
Section: Discussionsupporting
confidence: 74%
“…However, this theory is still debated, as a study by Mizrahi et al [41] failed to find any significant correlation between the presence of biofilm produced by non-typeable H. influenza and treatment failure or infectious recurrences in patients with AOM. These findings were supported by Osgood et al [42], who suggested that the aerobic conditions occurring during AOM episodes may limit biofilm formation.…”
Section: Nasopharyngeal Bacterial Biofilm: Is There a Correlation supporting
confidence: 74%
“…Nasal biofilms are associated with increased nasal resistance, a measure of nasal obstruction [20]. The otopathogen non-typable Haemophilus influenza requires anaerobic conditions to form biofilms [21], and may therefore be aided by nasal congestion. Although direct evidence that nasal and nasopharyngeal biofilms connect nasal obstruction to COME is lacking, adenoid hypertrophy in particular is a risk factor for nasal obstruction, snoring, and COME, with the preferred explanation being that adenoids can act as a reservoir for otopathogens [22, 23].…”
Section: Discussionmentioning
confidence: 99%